2022
DOI: 10.1007/s11356-022-22116-7
|View full text |Cite
|
Sign up to set email alerts
|

Advanced operational measure for reducing fuel consumption onboard ships

Abstract: Environmental issues and targets to reduce greenhouse gas emissions have reinforced attempts to increase energy efficiency for all stakeholders, including the shipping industry. International maritime organization (IMO) has prescribed operational and design measures to develop energy efficiency and decrease ship emissions, and one of the effective operational measures is trim optimization, which is a feasible measure because it does not necessitate ship structural modification or engine advancement, but it can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Optimizing a suitable speed while selecting an efficient propeller is another solution to reduce the fuel consumed, cavitation and noise, particularly when applying engine power limitation level to avoid engine overloading (Tadros et al, 2022d). Optimizing the trim conditions of the ship, so the ship can be trimmed by stern which is more effective than by trim bow in terms of resistance and therefore reduce fuel consumption accompanied by an increase in energy efficiency (Elkafas, 2022). This kind of selection allows the ship master to ensure lower resistance along the route.…”
Section: Ship Energy Efficiency Management Plan and Energy Efficiency...mentioning
confidence: 99%
“…Optimizing a suitable speed while selecting an efficient propeller is another solution to reduce the fuel consumed, cavitation and noise, particularly when applying engine power limitation level to avoid engine overloading (Tadros et al, 2022d). Optimizing the trim conditions of the ship, so the ship can be trimmed by stern which is more effective than by trim bow in terms of resistance and therefore reduce fuel consumption accompanied by an increase in energy efficiency (Elkafas, 2022). This kind of selection allows the ship master to ensure lower resistance along the route.…”
Section: Ship Energy Efficiency Management Plan and Energy Efficiency...mentioning
confidence: 99%
“…The International Maritime Organization (IMO) has developed several laws and guidelines to regulate greenhouse gas (GHG) emissions from ships, intending to reduce these pollutants by almost 30% by 2030 and 80% by 2040 compared to the pollutants produced in 2008 [1,2]. To achieve this goal, numerous operational and technological strategies have been developed to reduce greenhouse gas emissions and increase energy efficiency on board ships [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The research displayed that the emissions of ships in port can be reduced by 8.0–11.9% and the traffic efficiency can be improved by 3.8–6.2%. Moreover, the relationship between ship trim, fuel consumption, and the ship speed has been investigated by Elkafas ( 2022 ); the results revealed that the bow trim increases the fuel consumption at different ship speeds while the stern trim decreases the fuel consumption.…”
Section: Introductionmentioning
confidence: 99%